STUDY OF FAMILY CONVOLVULACEAE FROM KARJAT AND JAMKHED TEHSIL IN (AHMEDNAGAR) AHILYANAGAR DISTRICT (MS), INDIA - Jagtap C. L.; Avchar B. K. (The Bioscan, 2025)
The present study focuses on the collection, identification, classification, and documentation of the members of the plant family Convolvulaceae from the Karjat and Jamkhed area, Ahilyanagar (Ahmednagar), M.S., India. The present study of plants is important to understand their current knowledge of regional floristic diversity. The angiosperms are flowering plants with a great evolutionary history. They include near about 3,60,000 known species in globally. Unfortunately, several angiosperm species in our nation remain unexplored. It is commonly called the bindweeds or morning glories, a family of about 60 genera and more than 1,650 species. These species are primarily herbaceous vines, but also include trees, shrubs, and herbs. The tubers of several species are edible, the best known of which is the sweet potato. In this area, such kind of taxonomic work is not been carried out yet, therefore, we took this research work to find out floristic diversity. We carried out this taxonomic work from March 2022 to up till date. As per conventional taxonomic techniques, plant materials were collected, prepared as herbarium specimens, and documented at the research center. Of the 20 plant species that were collected during the field surveys were identified with the help of some authentic floras, i.e., the Flora of Presidency of Bombay Volume I, II, and III, and Flora of Ahmednagar district, taxonomic literature, and taxonomy experts.